Chemocoding as an identification tool where morphological- and DNA-based methods fall short: Inga as a case study - Endara M.-J.; Coley P.D.; Wiggins N.L.; Forrister D.L.; Younkin G.C.; Nicholls J.A.; Pennington R.T.; Dexter K.G.; Kidner C.A.; Stone G.N.; Kursar T.A. (My University, 2018)
The need for species identification and taxonomic discovery has led to the development of innovative technologies for large-scale plant identification. DNA barcoding has been useful, but fails to distinguish among many species in species-rich plant genera, particularly in tropical regions. Here, we show that chemical fingerprinting, or ‘chemocoding’, has great potential for plant identification in challenging tropical biomes. Using untargeted metabolomics in combination with multivariate analysis, we constructed species-level fingerprints, which we define as chemocoding. We evaluated the utility of chemocoding with species that were defined morphologically and subject to next-generation DNA sequencing in the diverse and recently radiated neotropical genus Inga (Leguminosae), both at single study sites and across broad geographic scales. Our results show that chemocoding is a robust method for distinguishing morphologically similar species at a single site and for identifying widespread species across continental-scale ranges. Given that species are the fundamental unit of analysis for conservation and biodiversity research, the development of accurate identification methods is essential. We suggest that chemocoding will be a valuable additional source of data for a quick identification of plants, especially for groups where other methods fall short. © 2018 The Authors. New Phytologist © 2018 New Phytologist Trust